2011
DOI: 10.1080/00140139.2011.596948
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive task demands, self-control demands and the mental well-being of office workers

Abstract: The cognitive task demands of office workers and the self-control demands of their work roles were measured in a sample of 196 employees in two different office layouts using a self-report questionnaire, which was circulated electronically. Multiple linear regression analysis revealed that both factors were associated with mental well-being, but not with physical well-being, while controlling for exposure to psychosocial stressors. The interaction between cognitive task demands and self-control demands had the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…They are used to reflect the amount of information used in working memory . In spite of the rating scale results can be affected by characteristics of respondents, like biases, response sets, errors, and protest attitudes [5,14], with the low cost and the ease of administration, as well as adaptability, have been found highly useful in a variety of domains such as industrial system , office working environment , and learning evaluation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are used to reflect the amount of information used in working memory . In spite of the rating scale results can be affected by characteristics of respondents, like biases, response sets, errors, and protest attitudes [5,14], with the low cost and the ease of administration, as well as adaptability, have been found highly useful in a variety of domains such as industrial system , office working environment , and learning evaluation .…”
Section: Discussionmentioning
confidence: 99%
“…They are used to reflect the amount of information used in working memory [28]. In spite of the rating scale results can be affected by characteristics of respondents, like biases, response sets, errors, and protest attitudes [5,14], with the low cost and the ease of administration, as well as adaptability, have been found highly useful in a variety of domains such as industrial system [1,6,18,24,33], office working environment [3], and learning evaluation [4,11,15,30]. MWL assessment based on subjective ratings, such as the NASA-task load index (NASA-TLX) [8], subjective workload assessment technique (SWAT) [19], subjective workload dominance [27], workload profile (WP), etc., are becoming increasingly important as evaluation tools and have been widely used to assess the human MWL.…”
Section: Mental Workload Measurement Methodsmentioning
confidence: 99%
“…Yet it is still unclear whether cognitive failures make one susceptible to stress or if stress causes the cognitive failures. Bridger et al (39,40) found that self-reported cognitive failures were predictive of selfreported strain in the following two years. Furthermore, animal studies indicate that chronic stress affects several brain functions including memory (41,42).…”
Section: Stress and Cognitionmentioning
confidence: 99%
“…Most of the attention in the past few decades has been on open-plan offices and individual cognition (e.g. Bridger & Brasher, 2011;Roper & Juneja, 2008;Sundstrom, Town, Brown, Forman, & McGee, 1982). For example, Roper and Juneja (2008) argue that open-plan offices may heighten individual arousal and improve task performance via the social facilitation effect, but may also promote cognitive overload through crowding, office noise, distractions, and interruptions.…”
Section: Research Issuesmentioning
confidence: 99%